PENGARUH SUMBER DAYA MANUSIA, SISTEM INFORMASI, DAN KOMITMEN ORGANISASI TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Empiris pada SKPD Kabupaten Siak) - Desti Widiart; Rita Anugerah; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine and analyze on (1) The effect of human resources working in the finance department in the SKPD to the adoption of accrual-based government accounting standards in Siak, (2) The effect of the information system that has been applied to the adoption of accrual-based government accounting standards in Siak (3) The effect of existing organizational commitment towards the implementation of accrual-based government accounting standards in Siak. This research was conducted in Siak using primary data, namely the data from questionnaires filled out by respondents. The objects used in this study is a working unit (SKPD) in Siak district government. The population in this study were employees of the financial section in Siak district government. Respondents were selected using purposive sampling, data analysis in this study using multiple linear regression model. While processing the data in this study using SPSS 21. The results showed that the variables of human resources effect the implementation of accrual based government accounting standards. While variable information systems and organizational commitment has no effect on the application of accrual-based government accounting standards.Keywords : government accounting standards, accrual based, the application of accrual based government accounting standard, the human resources, the information system, and the commitment of organization